Reducing sugary drink intake through youth empowerment: results from a pilot-site randomized study - Monica L. Wang; Marisa Otis; Milagros C. Rosal; Christina F. Griecci; Stephenie C. Lemon (BMC, 2019)
Abstract Background Efficacious strategies to reduce sugar-sweetened beverage (SSB) consumption among youth are needed. This pilot study assessed the feasibility and preliminary efficacy of a community-based youth empowerment intervention to reduce SSB consumption and obesity risk among a low-income, ethnically diverse sample of youth. Methods The H2GO! intervention was pilot-tested in an afterschool setting (Boys and Girls Clubs (BGC)) in Massachusetts, USA. One site was randomized to receive the intervention; the other site received standard programming. Youth ages 9-12 years and their parents/caregivers were eligible to participate. A total of N = 110 parent-child pairs (N = 55 parent-child pairs per site) were recruited. The 6-week intervention consisted of group-based weekly sessions delivered by trained BGC staff and youth-led activities that engaged parents. Child outcomes included self-reported SSB and water intake and measured body mass index z scores (zBMI). Parent outcomes included self-reported SSB and water intake, SSB purchasing, and availability of SSBs at home. Outcomes were measured at baseline, 2 months, and 6 months. Generalized linear and logistic regression models were used to estimate intervention effects over time. Results The final analytic study sample consisted of 100 child participants (38% Black, 20% Hispanic, 13% White, 12% Multiracial, 11% Asian) and 87 parent participants (78.2% female; 78.2% reporting eligibility for the free-or-reduced price lunch program). 6-month retention rates were ≥ 82%. Intervention attendance rates among intervention child participants (N = 51) averaged 78.1% (SD = 10.3). Over half (56.0%) of child participants were overweight or obese at baseline. Relative to the comparison site, intervention site child participants had decreased SSB intake (β = − 1.64; 95% CI: 2.52, − 0.76), increased water intake (β = 1.31; 95% CI: 0.38, 2.23), and decreased zBMI (− 0.23 units; 95% CI: − 0.31, − 0.14) over 6 months (p < 0.001). Intervention parent participants also reported decreased SSB intake (β = − 1.76; 95% CI: − 2.56, − 0.96) and increased water intake (β = 1.75; 95% CI: 1.11, 2.40) than comparison parent participants at 6 months (p < 0.001). Conclusions Findings demonstrate the potential of a youth empowerment intervention on reducing SSB intake and zBMI among a diverse sample. Findings will guide a larger cluster-randomized controlled trial to test intervention efficacy on preventing childhood obesity, as well as inform future interventions that aim to target additional diet and physical activity behaviors through youth empowerment. Trial registration ClinicalTrials.gov NCT02890056. Registered 31 August 2016.